Analisis Pengaruh Kualitas Layanan Untuk Meningkatkan Loyalitas Nasabah KSP Tunas Artha Mandiri Cabang Caruban Kabupaten Madiun - Dwi Wibowo (Universitas Islam Kadiri, 2020)
The purpose of this research to examine: (1) How influence tangibility on customer loyalty (2) How influence reliability to customer loyalty (3) How influence of responsiveness to customer loyalty (4) How influence of assurance to customer loyalty (5) How influence empathy to loyalitas (6) How influence tangibility, reliability, responsiveness, Assurance and emphaty together to customer loyalty (7) Which variable is relatively more dominant influence on customer loyalty. The subject of this research is KSP Tunas Artha Mandiri Caruban Branch of Madiun District with 41 customer respondents. The method used in this research is quantitative approach. Research data obtained by questionnaire technique, observation, documentation. The analysis technique used is multiple linear regression with F test and t test for testing some research hypothesis. The results showed that, with the validity, reliability and classic assumption test, hypothesis t test proved tangibility, responsiveness, assurance and empathy reliability had positive and significant effect on customer loyalty. The F test hypothesis proves that together, multiple regression model strengthens correlational correlation tangibility, responsiveness, reliability, assurance and empathy to customer loyalty.